2020
DOI: 10.1126/sciadv.abc9920
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic and parallel processing of visual threats in the retina control defensive responses

Abstract: Approaching predators cast expanding shadows (i.e., looming) that elicit innate defensive responses in most animals. Where looming is first detected and how critical parameters of predatory approaches are extracted are unclear. In mice, we identify a retinal interneuron (the VG3 amacrine cell) that responds robustly to looming, but not to related forms of motion. Looming-sensitive calcium transients are restricted to a specific layer of the VG3 dendrite arbor, which provides glutamatergic input to two ganglion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 64 publications
(121 reference statements)
2
37
0
Order By: Relevance
“…Although few studies have observed BC motion sensitivity, evidence of this feature of BCs is pervasive in the literature in the form of voltage-clamp recordings of glutamatergic synaptic input to RGCs and ACs. In the mouse retina, the glutamatergic input to both SACs and VG-luT3 ACs recorded in response to looming vs. receding stimuli exhibited a strong looming preference (6,32,47), and apparent motion stimuli elicited asymmetric glutamatergic inputs in RGCs (55). In the primate retina, glutamatergic inputs to several types of RGCs were demonstrated to exhibit motion sensitivity (81,86).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although few studies have observed BC motion sensitivity, evidence of this feature of BCs is pervasive in the literature in the form of voltage-clamp recordings of glutamatergic synaptic input to RGCs and ACs. In the mouse retina, the glutamatergic input to both SACs and VG-luT3 ACs recorded in response to looming vs. receding stimuli exhibited a strong looming preference (6,32,47), and apparent motion stimuli elicited asymmetric glutamatergic inputs in RGCs (55). In the primate retina, glutamatergic inputs to several types of RGCs were demonstrated to exhibit motion sensitivity (81,86).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, there was very little directional preference for any cluster in response to stimulation across the full RF. We also found that motion origin sensitivity was not limited to the moving bar stimulus, but that motion-sensitive BCs also preferred looming stimuli to receding stimuli (Fig- 232 ure S3a), suggesting that specific BC types might be impor-233 tant for several types of motion sensing tasks that are known 234 to be performed within the retina (4,6,10). nomenon observed throughout the mammalian visual system (i.e.…”
Section: Introduction 23mentioning
confidence: 84%
See 1 more Smart Citation
“…Only a subset of OFF bipolar cells receives direct input from rods, namely types 3a, 3b, and 4 in mouse retina (Behrens et al, 2016 ). These stratify in sublamina a of the IPL, just below the cholinergic a band, well-placed to contact OFF alpha ganglion cells, which have been associated with escape behavior in mice (Münch et al, 2009 ; Kim et al, 2020 ). A looming stimulus, such as a hawk, may present as a dark approaching object against a lighter background of sky, i.e., an OFF stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…92 One recent study showed that VG3 amacrine cells, which feed into several RGC circuits, respond to expanding shadows and thus may be involved in predator detection as well. 93 Overall, this indicates that predator detection presumably relies on multiple RGC channels, including some with small and some with larger RF sizes.…”
Section: Bias Toward Dark Contrastsmentioning
confidence: 96%